Valorization of Tropical Agricultural Waste Into Sustainable Additives for Water-Based Drilling Mud: A Case Study of Orange Peel and Durian Rind - Le, Nguyen Hai Nam; Ly, Trung Hieu; Dinh, Phuoc Hau (Scientific Contributions Oil and Gas, 2025)
This study explores the potential of orange peel powder (OPP) and durian rind powder (DRP) as biodegradable additives in water-based drilling mud. These agricultural wastes are processed into fine powders (<45 μm) and are characterized using FTIR, XRD, and SEM to determine their chemical functionality, crystallinity, and morphology. Both additives are incorporated into the base mud at concentrations of 2-8 g per 350 mL, and their rheological and filtration properties are evaluated. Due to its hydrophilic polymer content and microstructure, OPP significantly enhances apparent viscosity, yield point, and gel strength. DRP demonstrates superior performance in filtration control, reducing fluid loss by up to 40.3% and filter cake permeability by 60.2%. Visual and quantitative observations confirm that both additives improve the compactness of the filter cake and sealing efficiency. These results highlight the potential of OPP and DRP as eco-friendly, cost-effective alternatives to conventional chemical additives, supporting waste valorization and sustainable drilling operations.